Rapid Multiplexed Proteomic Screening for Primary Immunodeficiency Disorders From Dried Blood Spots - Collins, Christopher J.; Chang, Irene J.; Jung, Sunhee; Dayuha, Remwilyn; Whiteaker, Jeffrey R.; Segundo, Gesmar R. S.; Torgerson, Troy R.; Ochs, Hans D.; Paulovich, Amanda G.; Hahn, Si Houn (Frontiers in Immunology, 2018)
Background: Primary immunodeficiency disorders (PIDD) comprise a group of life-threateningcongenital diseases characterized by absent or impaired immune responses. Despite the fact that effective, curative treatments are available with optimal clinical outcomes when diagnosed early, newborn screening does not exist for the majority of these diseases due to the lack of detectable, specific biomarkers or validated methods for population-based screening. Peptide immunoaffinity enrichment coupled with selected reaction monitoring mass spectrometry (immuno-SRM) is a sensitive proteomic assay that allows for concurrent quantification of multiple analytes, conferring promising potential for newborn screening of PIDDs that lead to diminished or absent target proteins in the majority of cases. Objective: To determine and evaluate if a multiplex assay based on immuno-SRM is able to reliably and precisely distinguish affected patients with X-linked agammaglobulinemia (XLA), Wiskott-Aldrich Syndrome (WAS), and CD3ɛ-associated severe combined immunodeficiency (SCID) from one another and from unaffected normal control dried blood spot (DBS) samples. Methods: We performed a blinded, multiplexed analysis of proteolytically-generated peptidesfrom WASp, BTK, and CD3ɛ (for WAS, XLA, and SCID, respectively) in DBS samples from 42PIDD patients, 40 normal adult controls, and 62 normal newborns. The peptide of ATP7B 1056 was simultaneously monitored for quality assurance purpose. Results: The immuno-SRM assays reliably quantified the target peptides in DBS and accurately distinguished affected patients from normal controls. Analysis of signature peptides found statistically significant reduction or absence of peptide levels in affected patients compared to control groups in each case ((WAS and BTK: p = 0.0001, SCID: p = 0.05). Intra and inter-assay precision ranged from 11 - 22% and 11 - 43% respectively; linearity (1.39 – 2000 fmol peptide), and stability (≤0.09% difference in 72 h) showed high precision for the multiplexed assay. Inter-laboratory assay comparison showed high concordance for measured peptide concentrations, with R2 linearity ≥ 0.97 for the WAS 274, CD3e 197, BTK 407 and ATP7B 1056 peptides. Conclusion: Immuno-SRM-based quantification of proteotypic peptides from WASp, BTK, and CD3ɛ in DBS distinguishes relevant PIDD cases from one another and from controls, raising the possibility of employing this approach for large-scale multiplexed newborn screening of selective PIDDs.